Cardiac remodeling in obesity and after bariatric and metabolic surgery; is there a role for gastro-intestinal hormones?. (2nd November 2019) - Sanches, Elijah; Timmermans, Marieke; Topal, Besir; Celik, Alper; Sundbom, Magnus; Ribeiro, Rui; Parmar, Chetan; Ugale, Surendra; Proczko, Monika; Stepaniak, Pieter S.; Pujol Rafols, Juan; Mahawar, Kamal; et al.
ABSTRACT: Introduction : Obesity is associated with various diseases such as type 2 diabetes, hypertension, obstructive sleep apnea syndrome (OSAS), metabolic syndrome, and cardiovascular diseases. It affects several organ systems, including the pulmonary and cardiac systems. Furthermore, it induces pulmonary and cardiac changes that can result in right and/or left heart failure. Areas covered : In this review, authors provide an overview of obesity and cardiovascular remodeling, the individual actions of the gut hormones (like GLP-1 and PYY), the effects after bariatric/metabolic surgery and its influence on cardiac remodeling. In this review, we focussed and searched for literature in Pubmed and The Cochrane library (from the earliest date until April 2019), regarding cardiac function changes before and after bariatric surgery and literature regarding changes in gastrointestinal hormones. Expert opinion : Regarding the surgical treatment of obesity and metabolic diseases there is recognition of the importance of both weight loss (bariatric surgery) and improvement in metabolic milieu (metabolic surgery). A growing body of evidence further suggests that bariatric surgical procedures [like the Sleeve Gastrectomy (SG), Roux-en Y Gastric Bypass (RYGB), or One Anastomosis Gastric Bypass (OAGB)] have can improve outcomes of patients suffering from a number of cardiovascular diseases, including heart failure.